An Analysis on the Effect of Farmer Attitude towards Income in Livestock Enterprises of Tegal Ducks in the Pesurungan Lor Village of Tegal City - D. K. Taufik; . Isbandi; M. Dyah (Jurnal Ilmu dan Teknologi Peternakan, 2013)
The purpose of this research was to determine the effect of the duck farmer’s attitude on their income in livestock enterprises of Tegal ducks. Income was measured by the Revenue Cost Ratio,  which is the ratio between revenues and expenditures cost that will show the level of profit achieved. The research was conducted in October to November 2012, in Gapoktan Purwadiwangsa, Pesurungan Lor Village, Margadana District, city of Tegal. This research was carried out using the survey method and observation method. The determination of respondent size was done using simple random sampling of as many as 100 duck farmers.  The analysis of data was performed using the linear regression model of Y = β 0 + βX + δ with SPSS version 17.0. The variables in this research were, Y = Income (Revenue Cost Ratio), and X = Attitude of farmers . The research results showed that the average duck farmer display attitude (cognitive, affective and psycomotoric) in the good category. The average income was Rp 28.822.292  with an average business scale of 511 heads. The profit for each duck was Rp 56.403, and with a Revenue Cost Ratio (RCR) of 1,25, it meant the farmers ducks profited 25% per period. The attitude of duck farmers affected income by as much as 59.6%.